Observation of Robust Polarization Squeezing via the Kerr Nonlinearity in an Optical Fiber. Issue 3 (26th January 2023) - Kalinin, Nikolay; Dirmeier, Thomas; Sorokin, Arseny A.; Anashkina, Elena A.; Sánchez‐Soto, Luis L.; Corney, Joel F.; Leuchs, Gerd; Andrianov, Alexey V.
Abstract: Squeezed light is one of the resources of photonic quantum technology. Among the various nonlinear interactions capable of generating squeezing, the optical Kerr effect is particularly easy‐to‐use. A popular venue is to generate polarization squeezing, which is a special self‐referencing variant of two‐mode squeezing. To date, polarization squeezing generation setups have been very sensitive to fluctuations of external factors and have required careful tuning. In this work, a development of a new all‐fiber setup for polarization squeezing generation is reported. The setup consists of passive elements only and is simple, robust, and stable. More than 5 dB of directly measured squeezing is obtained over long periods of time without any need for adjustments. Thus, the new scheme provides a robust and easy‐to‐set‐up way of obtaining squeezed light applicable to different applications. The impact of pulse duration and pulse power on the degree of squeezing is investigated. Abstract : Squeezed light is a photonic quantum technology resource. The optical Kerr effect is often used to generate polarization squeezing. Such setups have been very sensitive to fluctuations of external factors. Here, a new all‐fiber very stable passive setup generating more than 5 dB of squeezing is presented. It provides a robust and easy way of obtaining squeezed light for applications.